Fecundity of thrips (Megalurothrips spp.) on long bean (Vigna unguiculata) / Anisah Mohammed … [et al.] - Mohammed, Anisah; Yusop, Mohamad Amir Shah; Abdul Aziz, Noorshilawati; Abdullah, Nur Suraya (2011)
Thrips is relatively small, less than 2 mm in size and considered as a serious insect pest to ornamental, vegetable, and fruit crops. Thrips belong to the insect order of Thysanoptera. These insect pests are causing major damage to the crop directly and indirectly. In this study, an experiment has been conducted to determine the fecundity of thrips. The host plants that were used in the study were long bean (Vigna unguiculata). The objective of this study was to determine the fecundity of female thrips. Result found that the maximum number of offspring produced by one pair of thrips was 14. The result obtained can be a useful information as a baseline data in order to formulate Integrated Pest Management (IPM) of controlling techniques such as in selecting types of insecticide, mode of action and also a combination of other techniques such as biological control.